Replacement names for Beckius Dechambre, 1992 and Syrictes Prell, 1936, and validation of Neoryctes Arrow, 1908 (Coleoptera: Scarabaeidae: Dynastinae) - Allsopp, Peter G. (Zootaxa, 2022)
The names of three genera of Dynastinae (Coleoptera: Scarabaeidae) are reviewed. The New Guinea genus Beckius Dechambre, 1992 (Dynastini) is preoccupied, and Debeckius Allsopp, new replacement name, is proposed. This results in Debeckius beccarii beccarii (Gestro, 1876), new combination, Debeckius beccarii koletta (Voirin, 1978), new combination, and Debeckius beccarii ryusuii (Nagai, 2006), new combination. The African genus Syrictes Prell, 1936 (Phileurini) is preoccupied, and Kirprellius Allsopp, new combination, is proposed. This results in Kirprellius curvicornus (Endrődi, 1977), new combination, Kirprellius dentatus (Prell, 1912), new combination, Kirprellius marceaui (Bouyer, 2020), new combination, Kirprellius rugulosus (Dupuis, 2013), new combination, and Kirprellius syrichtus (Fabricius, 1775), new combination. “Neoryctes Sclater, 1891” (Mammalia) is shown to be an invalid name and Neoryctes Arrow, 1908 (Pentodontini) remains the valid name for a dynastine genus from the Galápagos Islands, and Notoryctes Stirling, 1891 remains valid for the Australian marsupial moles.